2021
DOI: 10.3390/insects12090833
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temperature on the Development, Morphology, and Fecundity of Aenasius bambawalei (=Aenasius arizonensis)

Abstract: The effects of high temperature on the developmental, morphological, and fecundity characteristics of insects, including biological invaders and their accompanying natural enemies, are clear. Phenacoccus solenopsis (Homoptera: Pseudococcidae) is an aggressive invasive insect pest worldwide. Aenasius bambawalei (=Aenasius arizonensis Girault) (Hymenoptera: Encyrtidae) is a predominant accompanying parasitoid of this mealybug. Our previous studies showed that temperature change induced an increase in the female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Govindan & Hutchison, (2020) too had given similar results while studying the effect of temperature on brown marmorated stink bug (Halyomorpha halys) (Hemiptera: Pentatomidae) and observed that pre-oviposition period was longest at 20°C (32.67 ± 1.37 days) followed by that at 23°C and 27°C and shortest at 30°C and 33°C and ranged from 10.84 to 11.54 days. The longer pre-oviposition period at low temperature in our studies may be associated with longer time required for ovaries development (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 64%
“…Govindan & Hutchison, (2020) too had given similar results while studying the effect of temperature on brown marmorated stink bug (Halyomorpha halys) (Hemiptera: Pentatomidae) and observed that pre-oviposition period was longest at 20°C (32.67 ± 1.37 days) followed by that at 23°C and 27°C and shortest at 30°C and 33°C and ranged from 10.84 to 11.54 days. The longer pre-oviposition period at low temperature in our studies may be associated with longer time required for ovaries development (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 64%
“…Variation in food nutrient contents can lead to differences in insect nutrient content, resulting in modified growth, development, and reproduction of insects ( Cao et al 2015 , Qin et al 2017 ). Nutritional indexes can reflect the host plant’s suitability for insects ( Zhang et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“… Lv et al (2021) revealed that rearing Cnaphalocrocis medinalis at 34°C results in remarkably lower fecundity than those at 18°C and 22°C. Rearing of Aenasius bambawalei at 36°C results in fast gonad development, increased egg and sperm production, and enhanced reproduction capacity ( Zhang et al, 2021 ). However, the frequency and intensity of extreme heat events are increasing ( Ma and Ma, 2016 ), insects experience short and extreme heat rather than constant heat, and extreme heat may drive insect responses to climate change more than average temperature in the context of global warming ( Ma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%